Development of tourism through the formation of the image of Аstana (Nur-Sultan) as a “brand city” - Sadykova, D.A. (Fundamental and Experimental Biology, 2022)
In a global world, competition has developed not only between countries and companies, but also between cities and economic regions. Marketing, which is one of the most important elements of competition, is significant not only for the country’s Reputation, Economy, International Tourism, gaining the honor of attracting foreign investors, but also for the state as a whole, as well as for sub-economic regions called “local lands”. In recent years, the growing branding of the city and the brand the concept of the city has become one of the paramount topics accepted internationally. Alongside the concept of the “brand city”originating from the Dutch language, local branding, local marketing and local sales demonstrate a high level of influence of the “brand city”. In fact, each city is a brand that stands out for its geographical features, products, recreational resources, urban planning, or historical values. Each city on earth has its characteristics and differences. However, not all brands have the same value for cities. The recognition of the achievements of the city “branding”is related to the recognition of the achievements of the region and the state. Being a “brand city”is also considerable for the competitiveness of state tourism. Kazakhstan is one of the countries with the highest tourist potential at the world level. There are many cities in the country that have natural and historical features. The identification of the features of one of the new and dynamic cities of Kazakhstan —Astana (Nur-Sultan) as a “brand city” — will be the basis for applying it as a model for other cities of thestate. At the same time, branding of cities of Kazakhstan, as well as well-known brand cities of many major countries, paves the way for the promotion in the world.